INTEGRATED FACTORS INFLUENCING THE PUBLIC ADMINISTRATION SYSTEM - Cherviakova O.V. (Pressing Problems of Public Administration, 2015)
Integrated system highlighted the factors influencing the self-organization of the public administration system. A method for use in the analysis and synthesis of strategic and programtargeted documents.